Evaluation of Biofilm Inhibitory Efficacy of Bacopa monnieri, Acalypha indica and Calotropis gigantea Extracts and their Combination Against Wound Colonizing Bacteria Pseudomonas aeruginosa and Staphylococcus Aureus: Pharmaceutical Science-Pharmacognosy & Phytochemistry - Tanimu, Habibu; Vijayan, Nadasha Koonath; O.S, Bindhu (International Journal of Life Science and Pharma Research, 2022)
Key factors in compromised wound healing primarily include bacterial colonization and infection. Extensive use of systemic antibiotics, preferred choice of treatment for clinically infected wounds, is often accompanied with emergence of bacterial resistance. Quorum sensing (QS), density dependent chemical communication, is emerging as a promising area of research since most infectious microorganisms operate this mechanism to realize their pathogenic potential. Foregoing research indicates the potential of studying medicinal plant extracts/components and their combinations as vital inhibitors of QS regulated virulence factors’ production. Our study aims to understand the potential of three plant extracts and their combinations as vital inhibitors of QS regulated virulence factor’s production by two wound pathogens and to achieve this our objectives are to perform their violacein inhibitory (on C. violaceum) and biofilm inhibitory properties (on Pseudomonas aeruginosa and Staphylococcus aureus). Minimum inhibitory concentration (MIC) of aqueous plant extracts against P aeruginosa and S aureus was performed (two-fold serial microdilution). Violacein inhibition was assayed using agar well diffusion while biofilm inhibition by crystal violet method. Organisms presented 5mg/ml (Bacopa monnieri ), 2.5mg/ml (Acalypha indica), and 2.5mg/ml (Calotropis gigantea) as MIC. Three sets of individual extract concentrations (sub-MIC in μg/ml) and their corresponding combinations were used for this study. Extracts exhibited more significant (P<0.0001) violacein inhibition in combination than individually. Biofilm inhibition by extracts’ combination was also significantly (P<0.001) higher than that of individual extracts indicating a possible positive herb-herb interaction of phytoconstituents (synergistic or complementary). The relative decrease in response to individual extracts in higher concentrations (set ’c’) by both organisms point to possible recalcitrance behavior generally exhibited by bacteria on exposure to higher antibacterial agents. The improved antibiofilm efficacy exhibited by this novel combination may serve as an alternative approach in managing wound colonization by biofilm-producing bacteria and hence faster-wound healing.